Exploring fashion geometric pattern design process using a semiotic method - Cui, Can; Shaari, Nazlina (RedFame Publishing, 2023)
In recent years, the rapid growth of the economy and increasing degree of globalization have led to a continuous increase in demand for cross-cultural design. To meet this demand, the academic community and the fashion industry have continuously analyzed and developed methods for providing cross-cultural fashion pattern design. This study explores a symbol-based fashion pattern design method. Several commonly used geometric patterns in fashion pattern design were selected as research objects, and a method of symbolizing patterns in fashion pattern design was proposed to suit cross-cultural design. When redesigning fashion geometric patterns, typical patterns are symbolized. The results showed that the processed samples exhibited good adaptability for design applications. Therefore, this study indicates that the symbolic method can be applied to fashion pattern design, and this design method can be further systematized to achieve cross-cultural fashion design.